Innovative financing for housing in sustainable growth: Modeling incremental financing strategies in housing - Peter A. Makachia (Kenya Bankers Association (KBA), 2015)
Economic development will greatly be boosted by supporting housing for urban dwellers in the country. Indeed, a well housed population will only advance other investments in more productive sectors like industry and agriculture. However, access to appropriate affordable housing has been and remains a mirage for the majority urban dwellers in the middle and low income brackets in Kenya.
Keywords: 330